Improving customer satisfaction through supply chain management best practices in fast food restaurant - Norhayati, Kasim Sulamat; Lee, Khai Loon (Penerbit UMP, 2022)
The completion of business environment in food services industry, specifically fast food restaurant is increasing. Thus, it is crucial to focus the level of customer satisfaction on every transaction